2019
DOI: 10.5194/nhess-2019-331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induced seismicity risk analysis of the hydraulic stimulation of a geothermal well on Geldinganes, Iceland

Abstract: Abstract. The rapid increase in energy demand in the city of Reykjavik has posed the need for an additional supply of hot water from deep geothermal energy. The deep hydraulic (re-)stimulation of well RV-43 on the peninsula of Geldinganes (north of Reykjavik) is an essential component of the plan implemented by Reykjavik Energy to meet this energy target. Hydraulic stimulation is often associated with fluid-induced seismicity, most of which is not felt on the surface, but which, in rare cases, can cause nuisan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…One possibility is considering the level of individual risk exposure rather than a cumulative impact on the region. For example, individual risk exposure has been considered for induced earthquakes caused by gas extraction in the Netherlands (Bommer et al., 2017; Crowley et al., 2017; van Elk et al., 2017) and for geothermal projects in Iceland (Broccardo et al., 2020). Individual risk has the advantage that no individual person would exceed a personal level of risk and could be used as additional information to better inform the red‐light thresholds for TLPs.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is considering the level of individual risk exposure rather than a cumulative impact on the region. For example, individual risk exposure has been considered for induced earthquakes caused by gas extraction in the Netherlands (Bommer et al., 2017; Crowley et al., 2017; van Elk et al., 2017) and for geothermal projects in Iceland (Broccardo et al., 2020). Individual risk has the advantage that no individual person would exceed a personal level of risk and could be used as additional information to better inform the red‐light thresholds for TLPs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous laboratory and field experiments focused on determining factors influencing the transition from seismic to a‐seismic slip during fluid injections (see Cappa et al., 2019; Guglielmi et al., 2015; Scuderi & Collettini, 2018; Tinti et al., 2016; Tzortzopoulos et al., 2021, among others). Seismic traffic‐light systems have been also proposed for minimizing seismicity and risks to acceptable levels (see Baisch et al., 2019; Bommer et al., 2006; Bommer et al., 2015; Bosman et al., 2016; Broccardo et al., 2020; Häring et al., 2008; Kwiatek et al., 2019; Verdon & Bommer, 2021; Walters et al., 2015). More recently, “cyclic stimulation” (Hofmann et al., 2018, 2019; Zang et al., 2019) and “fracture caging” (Frash et al., 2021) were proposed for limiting induced seismic events in geothermal energy projects.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and Chen (2018) performed a statistical analysis on the distance of observed seismic events induced by the Salton Sea GPP operation, and found that the magnitude of events located outside the defined ring of a GPP (radius of 2−5 km) is five times less than the ones located near the power plant. Broccardo et al (2020) estimated the seismic risk of the Geldinganes GPP in Iceland. Their study emphasized the need for reevaluation of the risk by using updated data throughout a power plant's activity.…”
Section: Introductionmentioning
confidence: 99%